EFFECT OF MULCH ON SOIL MOISTURE, TEMPERATURE, WEED INFESTATION AND RANGEENI LAC YIELD OF PALAS (BUTEA MONOSPERMA) IN JHARKHAND - R. K. SINGH; S. GHOSAL (The Bioscan, 2015)
A study was conducted during 2010-2013 to assess the effect of different mulching materials viz., black polythene, transparent polythene, grass mulch, soil mulch, lac mud and unmulched (control) on soil moisture, soil temperature, weed suppression and summer season (rangeeni) lac yield of palas (Butea monosperma) under rainfed conditions in the Research farm of ICAR-Indian Institute of Natural Resins and Gums, Ranchi. Results showed the highest soil moisture conservation in black polyethylene by 22.3, 14 and 27.5%over control for the year 2011, 2012 and 2013, respectively. Different mulching materials showed different effects on soil temperature.The maximum mean temperature (22.4ºC) was recorded under transparent mulch,while, the lowest soil mean temperature (20.2ºC) was recorded under grass mulch. Mean soil temperature under grass mulch was lower by 1.3, 2.5 and 2.8ºC compared to transparent polyethylene mulch for three years, respectively. Black polyethylene suppressed the maximum amount of weed (492.33 g m-2), whereas the suppression by transparent mulch was 132.54 g m-2., which was recorded to be the least. Lac yield showed no definite trend in any of the treatments during the study period.